The Validation Study of the Stress and Anxiety to Viral Epidemics−6 Scale Among Patients With Cancer in the COVID-19 Pandemic - Kim, Hyeyeong; Kim, Harin; Lee, Hyuk Joo; Cho, Eulah; Koh, Su-Jin; Ahmed, Oli; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
Introduction The study aimed to explore the psychometric properties of the Stress and Anxiety to Viral Epidemics-6 (SAVE-6) scale among patients with cancer who are in serious situations in the current COVID-19 pandemic. Methods The survey included questions on the participants’ demographic information, clinical history of cancer (including cancer type, stage, current treatment or diagnosis of complete remission), and scores on rating scales, including the SAVE-6 scale, Coronavirus Anxiety Scale (CAS), and the Patient Health Questionnaire-9 (PHQ-9). Results The confirmatory factor analysis (CFA) results determined that the model fits the single factor structure of the SAVE-6 scale among patients with cancer. The multi-group CFA showed that SAVE-6 can measure the anxiety response in a similar way across multiple variables, such as sex, presence of clinical depression, being in a state of complete remission, or currently undergoing cancer treatment. The SAVE-6 scale showed good reliability (Cronbach’s alpha = 0.819) and convergent validity with the rating scales, such as CAS [r = .348 (95% CI, .273–.419), p <.001] and PHQ-9 items score [r = .251 (95% CI, .172–.328), p <.001]. Conclusions This study confirms SAVE-6 as a reliable and valid rating scale for measuring the anxiety response of patients with cancer during the current COVID-19 pandemic.